Response of foliar feeding of nutrients on quality attribute of guava (Psidium guajava L.) cv. Chittidar and Allahabad Safeda. - Anjanawe, S. R.; Patidar, Abhishek; Kanpuure, R.N.; Kacholi, B.K.; Sharma, Asheesh; Rai, Ram Kumar (Current Horticulture, 2025)
The experiment was carried out at the Instructional cum Research Fruit Orchard, Department of Fruit Science. K.N.K. College of Horticulture, Mandsaur during 2017-18. The experiment was laid out in Factorial Randomized Block Design (FRBD) replicated three times. The treatment consist of two factor (A) varieity V1- Chittidar, V2- Allahabad Safeda and factor (B) nine levels of nutrients- No- Control, N1-Zinc sulphate @ 0.3%, N2- Zinc sulphate @ 0.4%,N3- Calcium nitrate @ 1%,N4- Calcium nitrate @ 2%,N5 -Potassium sulphate @ 1%,N6- Potassium sulphate @ 2%,N7- Boron @ 0.2%,N8- Boron @ 0.4%. Among, the variety, maximum TSS (11.590Brix), non-reducing sugar (4.39%) was found in Chittidar (V1) and the maximum, TSS/Acid ratio (36.79) , reducing sugar (5.62%) and ascorbic acid (156.84 mg/100 pulp)was recorded in Allahabad Safeda (V2) and the minimum acidity (0.32%) was observed in Allahabad Safeda (V2). With respect to foliar application of nutrients, the maximum, TSS (12.600Brix), non-reducing sugar (4.56%) and TSS/Acid ratio (43.77) was observed in N6 (Potassium sulphate @ 2%), the maximum reducing sugar (5.74%) ascorbic acid,(170.28mg/100 pulp) and total sugar (9.68%) was recorded in N8 (boron@0.4%) and the minimum, acidity (0.28%) was recorded in N2 (zinc sulphate @0.4%).